Isocitrate lyase as a molecular target for weed suppression : in silico, in vitro and in vivo approaches - Menezes, Paulo Vinícius Moreira da Costa, 1990- (2022)
Orientador: Prof.ª Dr.ª Emy Luiza Ishii-Iwamoto